Elucidating the inhibitory mechanism of yeast α-glucosidase by phytocompounds from Scoparia dulcis through in vitro and in silico approach - Murugan, Gopinath; Rajkumar, Divya Sangeetha; Kaliyaperumal, Malarvizhi; Ramdoss, Ramya; Natarajan, Sasirekha; Padmanaban, Rajashree (Journal of biomolecular structure & dynamics, 2023)
Antidiabetic activity of herb Scoparia dulcis Linn (SD) used in traditional medicine is well established, yet, the molecular mechanism is not understood. In this study, in vitro α-glucosidase inhibitory effects of SD aqueous extract and its kinetics were investigated and in silico analysis was carried out. SD showed potent inhibition of α-glucosidase with low IC 50 value (30 μg/mL). Enzyme kinetics analysis revealed the inhibition to be a mixed type of inhibition. From literature screening, we found that six compounds of SD to exhibit potent anti-diabetic activity, namely apigenin, betulinic acid, hispidulin, luteolin, scopadulcic-acid-B and scutellarein. These compounds were subjected to molecular docking. Docking studies revealed scopadulcic acid B and betulunic acid to show optimum binding constant and low free energy. Molecular dynamics simulation was carried out to further understand the interaction and stability between glucosidase and ligands of SD. Taken together, the study reveals that the potency of SD is due to synergistic effect of active phytochemicals in it and suggest that their properties can be utilized for anti-diabetic treatment strategies. Communicated by Ramaswamy H. Sarma